Dead Reckoning : The Story of How Johnny Mitchell and His Fighter Pilots Took on Admiral Yamamoto and Avenged Pearl Harbor - Lehr, Dick (New York, NY : Harper, an imprint of HarperCollinsPublishers, 2020)
"The definitive and dramatic account of what became known as "Operation Vengeance" -- the targeted kill by U.S. fighter pilots of Japan's larger-than-life military icon, Admiral Isoroku Yamamoto, the naval genius who had devised the devastating attack on Pearl Harbor."--
Includes bibliographical references (pages 385-388) and index.
Keywords: Mitchell, Johnny; Yamamoto, Isoroku, -- 1884-1943 -- Assassination; Yamamoto, Isoroku, -- 1884-1943; 1939-1945; Operation Vengeance, 1943.; World War, 1939-1945 -- Campaigns -- Pacific Area; World War, 1939-1945 -- Aerial operations; Assassination; Military campaigns; Military operations, Aerial; Pacific Area